ANALISIS PENINGKATAN MUTU MELALUI PENGENDALIAN PRODUK BAD DENGAN METODE SEVEN TOOLS PADA PROSES CORE CASTING PT STI - Isroni, Isroni (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This paper discusses the results of research on the method of continuous quality improvement. The object of the research is the product type process of Bath Shower Mixer Core Casting at PT STI, a company engaged in manufacturing that produces Sanitary equipment. The production of the Mixing Bath Shower Core Casting process in the October-December 2017 period showed a total production of 40,339 pieces with a bad level of 2,263 pieces (5.61%), while the minimum target set by the company was 5.5%. The dominant bad product problem is loss and breakage. Analysis and problem solving using the seven tool method with data collection, data stratification, determining the biggest problem to solve, analyzing the biggest problem factors, collecting and searching for dominant causes, making plans and improvements, monitoring the results of improvements, making new standards . The results of the analysis concluded that the problem that caused the decline in quality was loss and breakage. Loss problems due to engine factors, namely maximum wind pressure below 0.54 MPa. While the cause of rupture is a method factor that does not have a high standard between coveyor height and core mold surface which causes uneven and standard material factors for 265gr resin. After finding the cause of the porous problem, Diagphram DF70mm was repaired to produce a pressure of more than 0.54Mpa and a corrective action in the form of preventive maintenance every week. As for broken repairs, a high standard conveyor arrangement with a mold surface of 3.5 - 4.0 cm is made. After repairs to production in July-September 2018 the production amounted to 25,151 with a bad amount 1,325 pcs (5.27%).